1990
DOI: 10.1017/s0950268800048019
|View full text |Cite
|
Sign up to set email alerts
|

The time course of the immune response to experimental coronavirus infection of man

Abstract: After preliminary trials, the detailed changes in the concentration of specific circulating and local antibodies were followed in 15 volunteers inoculated with coronavirus 229E. Ten of them, who had significantly lower concentrations of pre-existing antibody than the rest, became infected and eight of these developed colds. A limited investigation of circulating lymphocyte populations showed some lymphocytopenia in infected volunteers. In this group, antibody concentrations started to increase 1 week after ino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

41
600
1
16

Year Published

1992
1992
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 625 publications
(658 citation statements)
references
References 31 publications
41
600
1
16
Order By: Relevance
“…Subsequently, repeated or intermittent nasal shedding episodes occurred in the same animal, with or without respiratory disease, but with transient increases in serum antibody titers consistent with reinfection. These findings suggest a lack of long-term mucosal immunity in the upper respiratory tract after natural respiratory BCoV infection, confirming similar observations for human 46 and porcine respiratory CoV infections. 47 Within a herd, reservoirs for respiratory BCoV infection may be virus cycling in clinically or subclinically infected calves, young adult cattle in which sporadic nasal shedding occurs, 16,24 or clinically or subclinically infected adults.…”
Section: Epidemiology and Interspecies Transmission Respiratory Bcovsupporting
confidence: 88%
“…Subsequently, repeated or intermittent nasal shedding episodes occurred in the same animal, with or without respiratory disease, but with transient increases in serum antibody titers consistent with reinfection. These findings suggest a lack of long-term mucosal immunity in the upper respiratory tract after natural respiratory BCoV infection, confirming similar observations for human 46 and porcine respiratory CoV infections. 47 Within a herd, reservoirs for respiratory BCoV infection may be virus cycling in clinically or subclinically infected calves, young adult cattle in which sporadic nasal shedding occurs, 16,24 or clinically or subclinically infected adults.…”
Section: Epidemiology and Interspecies Transmission Respiratory Bcovsupporting
confidence: 88%
“…It is theoretically possible that the use of a virus that may have been attenuated by laboratory growth and applied in an artificial way to the nose may result in a different illness to that seen in "wild" infections, but previous experimental inoculation studies have confirmed that the disease spectrum is that of wild-type infection [24,25]. Additionally, such a model lessens the problem of virus heterogeneity and timing of onset of infection that could make the detailed study of the physiological and biological responses to "wild" infections very difficult.…”
Section: Evidence Of Viral Infectionmentioning
confidence: 99%
“…Indeed, a convalescent to acute ratio in serum of 1.3 has been used previously as a cut-off indicating significant infection [13]. There are only two main serotypes of HCoV, both known to cause repeated infections in the same individuals [25]. In this respect, HCoV is very different from RV, where there are several hundred known serotypes that have the ability to induce a four-fold rise in antibody levels in immune-naive individuals.…”
Section: Evidence Of Viral Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of rhinoviruses, for instance, specific protective antibody re sponses usually follow interactions, and the antibodies persist and apparently confer protection against reinfec tion and disease. But there are so many serotypes that fur ther infections often occur, and a high proportion of these give rise to disease, so illnesses due to rhinoviruses con tinue throughout life [2], Some viruses, like coronavi ruses, seem to produce a less persistent immune response and are able to infect even when some antibody is present, and so it is possible to be re-infected with the same, or a very similar, type of coronavirus after the lapse of a year or two; so for rather different reasons we often suffer from coronavirus colds [3], there was enthusiasm to found the Common Cold Unit in 1946. At the moment, little notice is taken of this aspect of colds but there is evidence from work on volunteers that colds cause measurable defects in the performance of tasks requiring, for instance, attention or hand-eye coor dination [4].…”
mentioning
confidence: 99%